The Generalization of some Problems in Calculus of Variations into the Space of Analytic Functions (Latakia University Journal -Basic Sciences Series, 2018)
This paper deals with the following conditional extremal problem: Find the minimum value of the integral functional under some boundary conditions and additional constraints of type , where   is some function defined in Banach Space of  holomorphic functions in unit disc and  is a regular curve in this disc. It have been shown that the solution  of the above  problem satisfies the system of differential equations Where  and  are the Lagrange Multipliers.Some applications and additional examples are given.